PENGARUH PERTUMBUHAN EKONOMI DAN PERTUMBUHAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN BERAU: PENGARUH PERTUMBUHAN EKONOMI DAN PERTUMBUHAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN BERAU - Lisa Puspitasari (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
The influence of economic growth and investment growth on employment in Berau district. The aim of this research is to find out how much influence economic growth and investment growth have on employment in Berau district. This research uses Multiple Linear Regression analysis tool with secondary research data.